2016
DOI: 10.1177/1553350616672963
|View full text |Cite
|
Sign up to set email alerts
|

Allowing New Opportunities in Advanced Laparoscopy Training Using a Full High-Definition Training Box

Abstract: This novel laparoscopic training box presents a high-resolution image and allows training different types of advanced laparoscopic procedures. The simulator box was positively assessed by experts and demonstrated to be effective for laparoscopy training in resident surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Two articles validated ST by face and content 25,26 both presented a BS training model. Bahsoun et al 25 proposed a cardboard-based model which replaced traditional laparoscopic camera with a tablet included 10 participants, and face validation was done by experienced laparoscopic surgeons that answered an evaluation form for tablet Feedback.…”
Section: Face and Content Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles validated ST by face and content 25,26 both presented a BS training model. Bahsoun et al 25 proposed a cardboard-based model which replaced traditional laparoscopic camera with a tablet included 10 participants, and face validation was done by experienced laparoscopic surgeons that answered an evaluation form for tablet Feedback.…”
Section: Face and Content Validitymentioning
confidence: 99%
“…This study researched components of a laparoscopic training setup and recreated a simplified, less expensive model based on the use of a tablet, to overcome the obstacle of laparoscopic stack and camera costs. 25 Achurra et al 26 presented a high-definition BS, in which 76 expert bariatric surgeons answered a four-item questionnaire for face validity, result showed that 98% considered that BS had a high fidelity and was optimum for advanced laparoscopic simulation. Content validity was evaluated by assessing improvements on global and specific rating scores of 15 first-year general surgery residents.…”
Section: Face and Content Validitymentioning
confidence: 99%
“…Spaced practice reduces mental fatigue, demands increased trainee effort to attain proficiency level at practice sessions and leads to better memory consolidation, with the subsequent efficient learning. Simulation and spaced practice have been shown to improve acquisition of skills with a decrease in surgical adverse events in laparoscopic surgery training (57)(58)(59)(60). Continued learning with the goal to improve procedure skills beyond a year of IP fellowship training can be challenging.…”
Section: Competency and Mastery Learningmentioning
confidence: 99%
“…The technical types of laparoscopic simulation system can be roughly divided into two kinds, namely the operation training and virtual reality simulators (Achurra et al, 2017;Jimbo et al, 2016 Virtual reality technology is a kind of technology that through the use of special electronic equipment and computer simulation of three-dimensional images, or environment interaction technology, medical virtual system combining computer software and force sensing device, making the surgeon in the virtual environment see the internal anatomical structure of human body clearly, and force feedback technology enhance the perception of surgical operation (Yiannakopoulou et al, 2015). At present there are mainly four kinds of virtual reality simulator: laparoscopy URTM system, Xitact LS500 laparoscopic simulators, lap mentor simulator and MIST-UR laparoscopic simulators (Zheng and Song, 2012).…”
Section: Overviewmentioning
confidence: 99%